(untitled) (Journal of Human Sciences, 2021)
Ghat, as well as the Ottoman Empire’s attempt to control it. France wanted to control the city for a long period of time, during its many attempts to communicate with the sheikhs and leaders in the city, and to conclude agreements and treaties with them as well as the Ottoman state. It is trying to impose control over the city and many cities in the Libyan south in order to secure the Libyan borders, especially after it sensed the danger from France when it occupied Algeria and thus became near it. Therefore, the Ottoman Empire sought to impose control over the city of Ghat, as the researcher touched upon the main factors that led To this competition for control of the city, the researcher also deals with the role of the French travelers in order to impose that control, especially the role of the traveler Henri Dvira. The research also deals with the political situation of the city of Ghat after it was subject to Ottoman control.